2004
DOI: 10.1002/aheh.200300532
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Bacteriological Water Quality in Mountainous Surface and Groundwaters

Abstract: The presence of pathogenic bacteria in water, along with the factors that act upon them, constitutes a field that has been little investigated in natural environments. It is clear, however, that these pathogens do have a significant effect on the quality of drinking water. Selected bacteria such as Salmonella, Campylobacter, Yersinia, and Listeria were searched for in groundwaters of mainly mountainous regions. Waters of one or two brooks in the catchment area of each spring were also analysed. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…This finding implies that against the backdrop of other potential human and wildlife sources of contamination, dairy operations, which can consist of dairy barns, pasture lands, manure lagoons, and manured fields, are significant contaminant sources. This finding is consistent with those of previous studies (49,51), suggesting that similar landscape attribute relationships might have affinities beyond those reported for the environmental setting discussed in this study. Overall, the seasonal distribution of L. monocytogenes in agricultural watersheds will likely depend on the timing of manure applications (spring being the most important period in temperate climates) and the access of animals on pasture to watercourses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding implies that against the backdrop of other potential human and wildlife sources of contamination, dairy operations, which can consist of dairy barns, pasture lands, manure lagoons, and manured fields, are significant contaminant sources. This finding is consistent with those of previous studies (49,51), suggesting that similar landscape attribute relationships might have affinities beyond those reported for the environmental setting discussed in this study. Overall, the seasonal distribution of L. monocytogenes in agricultural watersheds will likely depend on the timing of manure applications (spring being the most important period in temperate climates) and the access of animals on pasture to watercourses.…”
Section: Discussionsupporting
confidence: 93%
“…Lineage distribution of L. monocytogenes water isolates varied with the season. Temperature was previously shown to influence the distribution of serovars in surface waters, with serovar 1/2a being significantly associated with cold periods and serovar 4b being significantly associated with higher air temperatures (51). These findings are in agreement with our results, where lineage II (i.e., serovar 1/2a) isolates were dominant during the fall whereas lineage I (i.e., serovar 4b) isolates were dominant in the summer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, certain serotypes seem to be associated with different environmental niches (Lyautey et al, 2007;Schaffter et al, 2004) and patient conditions (McLauchlin, 1990) as discussed in more detail below.…”
Section: Lineage Classification By Phenotypic and Genotypic Methodsmentioning
confidence: 99%
“…Faecal bacteria may also occur in pristine ground and surface waters that are not impacted by human activity; they can be attributed to wild animals (Niemi and Niemi 1991). Recent research revealed that small numbers of microbial pathogens, such as Legionella, might be detectable in pristine waters without any discernible contamination source, and without the presence of faecal indicator bacteria (Brooks et al 2004;Schaffter et al 2004). In some cases, microbial pathogens thus seem to be part of the "natural" biocenosis in groundwater.…”
Section: Bioindicators For Groundwater Qualitymentioning
confidence: 99%